Attosecond physics in optical near fields - Heimerl, Jonas; Meier, Stefan; Herzig, Anne; López Hoffmann, Felix; Seiffert, Lennart; Lesko, Daniel; Hillmann, Simon; Wittigschlager, Simon; Weitz, Tobias; Fennel, Thomas; Hommelhoff, Peter (Nature Physics, 2025)
Attosecond science—the control of electrons by ultrashort laser pulses—is developing into lightfield-driven, or petahertz, electronics. Optical-field-driven nanostructures provide elements for such electronics, which rely on understanding electron dynamics in the optical near field. Here we report near-field-induced low-energy stripes in carrier-envelope-phase-dependent electron spectra—a spectral feature that appears in the direct electrons emitted from a strongly driven nanostructure. These stripes arise from the subcycle sensitivity of the ponderomotive acceleration of electrons injected into a strong near-field gradient by a few-cycle optical waveform. They allow the tracking of direct and rescattered electron emissions on subcycle timescales and provide access to the electron momentum width at emission. Because this effect occurs in the direct electron signal, a large fraction of the emitted electrons can be steered, enabling the isolation of individual attosecond electron bursts with high charge densit
Keywords: Nanophotonics and plasmonics; Nonlinear optics

Correlations in strong-field-emitted ultrashort electron pulses from metal needle tips - Meier, Stefan; Heimerl, Jonas; Hommelhoff, Peter (Laser Physics Letters, 2024)
When two electrons are emitted from a metal needle tip with the help of femtosecond laser pulses, they show a strong anticorrelation signal in the energy domain. Depending on the wavelength and intensity of the driving laser pulses, the electron emission process can be either in a perturbative regime, like single- or multi-photon photoemission, or in the strong-field regime, where emission is dominated by the instantaneous electric field of the laser pulse, or in the intermediate regime. Here, we report on the two-electron anticorrelation signal and how it evolves from the multiphoton toward the strong-field emission regime. We show that in both cases, the resulting anticorrelation signal can be well explained by semi-classical simulations using a point-particle model, thus the dynamics is dominated by the center-of-mass dynamics of the individual electrons. However, the actual emission process of multiple interacting electrons requires improved quantum mechanical models and therefore remains the subject of future work. This paper is part of the Special Topic Collection: papers from the 31th Annual International Laser Physics Workshop 2023 (LPHYS 2023

Coulomb Interactions and the Spatial Coherence of Femtosecond Nanometric Electron Pulses - Meier, Stefan; Hommelhoff, Peter (ACS Photonics, 2022)
The transverse coherence of electrons is of utmost importance in high resolution electron microscopes, point-projection microscopes, low-energy electron microscopy, and various other applications. Pulsed versions of many of these have recently been realized, mostly relying on femtosecond laser-triggering electron emission from a sharp needle source. We here observe electron interference fringes and measure how the interference visibility becomes reduced as we increase the emitted electron bunch charge. Due to the extremely strong spatiotemporal confinement of the electrons generated here, we observe the visibility reduction already at average electron bunch charges of less than 1 electron per pulse, owing to the stochastic nature of the emission process. We can fully and quantitatively explain the loss of coherence based on model simulations. Via the van Cittert-Zernike theorem, we connect the visibility reduction to an increase in the effective source size. We conclude by discussing emittance, brightness, and quantum degeneracy, which have direct ramifications to many setups and devices relying on pulsed coherent electrons.
CRIS-Team Scopus Importer:2022-09-09
Keywords: Coherence; Electron correlations; Electron interference; Electron optics; Femtosecond lasers; Ultrafast electron emission

Deep learning-based spatiotemporal multi-event reconstruction for delay line detectors - Knipfer, Marco; Meier, Stefan; Volk, Tobias; Heimerl, Jonas; Hommelhoff, Peter; Gleyzer, Sergei (Machine Learning: Science and Technology, 2024)
Accurate observation of two or more particles within a very narrow time window has always been a challenge in modern physics. It creates the possibility of correlation experiments, such as the ground-breaking Hanbury Brown-Twiss experiment, leading to new physical insights. For low-energy electrons, one possibility is to use a Microchannel plate with subsequent delay lines for the readout of the incident particle hits, a setup called a Delay Line Detector. The spatial and temporal coordinates of more than one particle can be fully reconstructed outside a region called the dead radius. For interesting events, where two electrons are close in space and time, the determination of the individual positions of the electrons requires elaborate peak finding algorithms. While classical methods work well with single particle hits, they fail to identify and reconstruct events caused by multiple nearby particles. To address this challenge, we present a new spatiotemporal machine learning model to identify and reconstruct the position and time of such multi-hit particle signals. This model achieves a much better resolution for nearby particle hits compared to the classical approach, removing some of the artifacts and reducing the dead radius a factor of eight. We show that machine learning models can be effective in improving the spatiotemporal performance of delay line detectors.
CRIS-Team Scopus Importer:2024-05-03
Keywords: delay; detector; line; machine learning; networks; neural; peak finder

Femtosecond Laser-Induced Electron Emission from Nanodiamond-Coated Tungsten Needle Tips - Tafel, Alexander; Meier, Stefan; Ristein, Jürgen; Hommelhoff, Peter (Physical Review Letters, 2019)
We present femtosecond laser-induced electron emission from nanodiamond-coated tungsten tips. Based on the shortness of the femtosecond laser pulses, electrons can be photoexcited for wavelengths from the infrared (1932 nm) to the ultraviolet (235 nm) because multiphoton excitation becomes efficient over the entire spectral range. Depending on the laser wavelength, we find different dominant emission channels identified by the number of photons needed to emit electrons. Based on the band alignment between tungsten and nanodiamond, the relevant emission channels can be identified as specific transitions in diamond and its graphitic boundaries. It is the combination of the character of initial and final states (i.e., bulk or surface-near, direct or indirect excitation in the diamond band structure), the number of photons providing the excitation energy, and the peak intensity of the laser pulses that determines the dominant excitation channel for photoemission. A specific feature of the hydrogen-terminated nanodiamond coating is its negative electron affinity that significantly lowers the work function and enables efficient emission from the conduction band minimum into vacuum without an energy barrier. Emission is stable for bunch charges of up to 400 electrons per laser pulse. We infer a normalized emittance of <0.20 nm rad and a normalized peak brightness of >1.2×1012 A m−2 sr−1. The properties of these tips are encouraging for their use as laser-triggered electron sources in applications such as ultrafast electron microscopy as well as diffraction and novel photonics-based laser accelerators.<br
Keywords: diamond-coated nanotip; ultrafast electron sources; emittance; brightness; electron microscopy

Few-electron correlations after ultrafast photoemission from nanometric needle tips - Meier, Stefan; Heimerl, Jonas; Hommelhoff, Peter (Nature Physics, 2023)
Free electrons are essential in such diverse applications as electron microscopes, accelerators and photoemission spectroscopy. However, the space charge effects of many electrons are often a problem and, when confined to extremely small space–time dimensions, even two electrons can interact strongly. Here we demonstrate that the resulting Coulomb repulsion can be highly advantageous, as it leads to strong electron–electron correlations. We show that femtosecond laser-emitted electrons from nanometric needle tips are highly anticorrelated in terms of energy because of dynamic Coulomb repulsion, with a visibility of 56%. We extract a mean energy splitting of 3.3 eV and a correlation decay time of 82 fs. The energy-filtered electrons display a sub-Poissonian number distribution with a second-order correlation function as small as g (2) = 0.34, implying that shot-noise-reduced pulsed electron beams can be realized by simple energy filtering. We also reach the strong-field regime of laser-driven electron emission and gain insights into how the electron correlations of the different electron classes (direct or rescattered) are influenced by the strong laser fields.
Created from Fastlane, Scopus look-up

From strong-field physics in and at nanoscale matter to photonics-based laser accelerators - Kozak, Martin; Higuchi, Takuya; McNeur, Joshua; Shiloh, Roy; Heide, Christian; Paschen, Timo; Yousefi, Peyman; Sturm, Constanze; Li, Ang; Illmer, Johannes; Meier, Stefan; Schönenberger, Norbert; et al. (205, 2019)
New ways of controlling quasi-free and free electrons by means of phase-controlled ultrashort laser pulses are demonstrated: from strong-field physics in the conducting 2-d material graphene and at the surface of nanostructures, to laser acceleration of free electrons with a nanophotonic structure, and the demonstration of the longitudinal Kapitza-Dirac effec

High spatial coherence in multiphoton-photoemitted electron beams - Meier, Stefan; Higuchi, Takuya; Nutz, Manuel; Högele, Alexander; Hommelhoff, Peter (Applied Physics Letters, 2018)
Nanometer-sharp metallic tips are known to be excellent electron emitters. They are used in highest-resolution electron microscopes in cold field emission mode to generate the most coherent electron beam in continuous-wave operation. For time-resolved operation, sharp metal needle tips have recently been triggered with femtosecond laser pulses. We show here that electrons emitted with near-infrared femtosecond laser pulses at laser oscillator repetition rates show the same spatial coherence properties as electrons in cold field emission mode in cw operation. From electron interference fringes, obtained with the help of a carbon nanotube biprism beam splitter, we deduce a virtual source size of less than (0.65 ± 0.06) nm for both operation modes, a factor of ten smaller than the geometrical source size. These results bear promise for ultrafast electron diffraction, ultrafast electron microscopy, and other techniques relying on highly coherent and ultrafast electron beam
Keywords: ultrafast electron sources; metallic needle tips; spatial coherence; femtosecond pulses; source size estimation

Multiphoton electron emission with non-classical light - Heimerl, Jonas; Mikhaylov, Alexander; Meier, Stefan; Höllerer, Henrick; Kaminer, Ido; Chekhova, Maria; Hommelhoff, Peter (Nature Physics, 2024)
Photon number distributions of classical and non-classical light sources have been studied extensively, yet their impact on photoemission processes is largely unexplored. In this article, we present measurements of electron number distributions from metal needle tips illuminated with ultrashort light pulses with various photon quantum statistics. By varying the photon statistics of the exciting light field between classical (Poissonian) and quantum (super-Poissonian), we demonstrate that the measured electron distributions are changed substantially. Using single-mode bright squeezed vacuum light, we measure extreme statistics events with up to 65 electrons from one light pulse at a mean of 0.27 electrons per pulse—the likelihood for such an event equals 10−128 with Poissonian statistics. By changing the number of modes of the exciting bright squeezed vacuum, we can tailor the electron number distribution on demand. Most importantly, our results demonstrate that the photon statistics is imprinted from the driving light to the emitted electrons, opening the door to new sensor devices and to strong-field optics with quantum light and electrons.<br
Keywords: Nanophotonics and plasmonics; Nonlinear optics; Quantum optics

Nonlinear scaling of strong field-driven multielectron emission - Heimerl, Jonas; Meier, Stefan; López Hoffmann, Felix; Wittigschlager, Simon; Lesko, Daniel; Hommelhoff, Peter (Journal of Vacuum Science & Technology B, Nanotechnology and Microelectronics, 2025)
When strong laser pulses in the near-infrared are focused on sharp needle tips, electrons can be emitted via multiphoton or optical tunneling emission. The emission yield scales nonlinearly. When emission yield and, in particular, its nonlinearity are plotted vs the laser intensity, the photo-emission regime can be identified: the nonlinearity decreases when going from the multiphoton to the optical tunneling regime. Such measurements are hampered by the fact that the transition from multiphoton to optical tunneling emission typically coincides with the transition from less than one electron emitted per laser pulse to more than one, meaning that space charge effects arise. We use a multi hit-capable detector to investigate these effects and find that the measured electron yield as a function of the intensity agrees perfectly with theoretical one-electron emission models, near field intensities up to 2.6 × 10 13 W cm − 2 (Keldysh- γ = 0.7 ), even though up to four electrons per laser pulse are detected. In particular, we observe a slope of over six in the multiphoton emission regime ( γ ≈ 1.6 ) and a slope as small as 2.8 for γ ≤ 1. Our results demonstrate that the electron emission is uncorrelated even in the tunneling regime with up to four electrons per two-cycle laser pulse and dominant contribution of two-electron events of 30 %. We also discuss how these data can be used as a valuable tool to determine the emission regime in which space charge effects can still be excluded. In the future, we expect such measurements to yield insights into emission beyond one electron models including correlation effects.
CRIS-Team Scopus Importer:2025-08-08

Optical measurement of the work function and the field reduction factor of metallic needle tips - Meier, Stefan; Heimerl, Jonas; Dienstbier, Philip; Hommelhoff, Peter (Review of Scientific Instruments, 2023)
Quintessential parameters for needle tip-based electron sources are the work function, the tip apex radius, and the field reduction factor. They determine the static emission properties and strongly influence laser-triggered photoemission experiments at these needle tips. We present a simple method based on photoemission with two different commonly available continuous-wave laser diodes to determine both parameters in situ. We demonstrate our technique at tungsten needle tips. In a first application, use the method to in situ monitor changes of the emitter caused by illumination with strong femtosecond laser pulses. After illumination, we observe an increase in the work function caused by laser-induced changes to the apex of the tip. These changes are reversible upon field evaporation and are accompanied by a change in the spatial electron emission distribution. We believe that this simple in situ work function determination technique is applicable to any metal and in many experimental settings.<br
Keywords: Work functions; Ultra-high vacuu; Field ion microscopy; Scanning electron microscopy; Femtosecond lasers; Optical materials; Optical metrology; Femtosecond electron pulse; Electron sources; Adsorption

Photoemission from an ultrabright and ultrafast LaB6 nanowire electron emitter studied at atomic scale - Li, Ang; Zhang, Han; Meier, Stefan; Tafel, Alexander; Hommelhoff, Peter (2021 34TH INTERNATIONAL VACUUM NANOELECTRONICS CONFERENCE (IVNC), 2021)
CRIS-Team WoS Importer:2022-02-04

PyCCAPT: A Python Package for Open-Source Atom Probe Instrument Control and Data Calibration - Monajem, Mehrpad; Ott, Benedict; Heimerl, Jonas; Meier, Stefan; Hommelhoff, Peter; Felfer, Peter (Microscopy Research and Technique, 2025)
Currently, the vast majority of atom probe instruments in use are commercial systems with closed, proprietary software. This is limiting for many experiments where low-level access to machine control, experiment data, or custom instrument setups is necessary. Over the past decade, advancements in off-the-shelf detector systems, fast data bus systems, and the availability of high-level programming languages such as Python have made it feasible to design and construct atom probe systems without extensive engineering expertise. Despite this progress, developing control system software, associated instruments, and data calibration algorithms remains a significant challenge for many projects. In this article, we introduce an atom probe control system that can be flexibly adapted to various hardware configurations. This system also includes essential instrument and experiment calibration algorithms, offering complete transparency to the user. This framework provides flexibility for innovative experiments and enhances calibration accuracy not possible with commercial systems. The methods and algorithms discussed are implemented in Python Control and Calibration for Atom Probe Tomography (PyCCAPT), which is an open-source solution for APT, addressing a gap in experimental control and data processing. While not compatible with commercial atom probes for data acquisition, its calibration module can be used for direct-flight-path systems and adapted for reflection-based instruments.
CRIS-Team Scopus Importer:2025-08-01
Keywords: atom probe control; atom probe data acquisition; atom probe raw data analysis; atom probe tomography; data calibration

Quantum light drives electrons strongly at metal needle tips - Heimerl, Jonas; Rasputnyi, Andrei; Pölloth, Jonathan; Meier, Stefan; Chekhova, Maria; Hommelhoff, Peter (Nature Physics, 2025)
Attosecond science relies on driving photoemitted electrons with the strong optical field of a laser pulse, which represents an intense classical coherent state of light. Bright squeezed vacuum is a quantum state of light that is also intense enough to drive strong-field physics. However, its mean optical electric field is zero, suggesting that, in a semi-classical view, electrons should not experience strong driving. The question arises if and how this quantum state of light can generate signatures of attosecond dynamics in strong-field photoemission. Here we show that the key signatures of strong-field physics—the high energy plateau and subsequent cut-off—also appear under driving of a needle tip by bright squeezed vacuum, but only when we post-select electron energy spectra on the individual photon number of each pulse. When averaging over many shots, we observe broad energy spectra without a plateau. This suggests that electrons driven by bright squeezed vacuum behave as if driven by an ensemble of coherent states of light. Our findings bridge strong-field physics and quantum optics, offering insights into bright squeezed vacuum and other quantum light states, and suggest the use of strongly driven electrons as quantum light sensor
Keywords: Attosecond science; Matter waves and particle beams; Single photons and quantum effects; Surfaces; interfaces and thin films

Statistics of multiphoton photoemission under coherent and non-classical illumination - Heimerl, Jonas; Mikhaylov, Alexander; Meier, Stefan; Höllerer, Henrick; Kaminer, Ido; Chekhova, Maria; Hommelhoff, Peter (Optics InfoBase Conference Papers, 2022)
We investigate experimentally how the photon statistics of light gets imprinted on multiphoton electron emission from needle tips. Coherent and bright squeezed vacuum light lead to entirely different electron statistics, matching with a quantum-optical analysis.
CRIS-Team Scopus Importer:2022-09-09

Strong field electron emission driven by a bright squeezed vacuum - Rasputnyi, Andrei; Heimerl, Jonas; Pölloth, Jonathan; Meier, Stefan; Tani, Francesco; Chekhova, Maria; Hommelhoff, Peter (2025 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2025, 2025)
The extreme light-matter interaction has brought unique tools for the subfemtosecond control of electron dynamics [1] and ultra-fast spectroscopy [2]. Until recently, the strong-field regime was accessible only with coherent states of light, which can be well described by classical electric fields when many photons are present (Fig. 1a). With the use of intense states of non-classical light, this situation has changed. New opportunities emerge with bright squeezed vacuum (BSV), which can be generated from optical parametric amplification of quantum vacuum fluctuations. Unlike classical light, BSV is a quantum superposition of coherent states with an amplitudes spanning a range from zero to very high values, up to ∼ 1 TW/cm2 [3]. BSV has a zero mean electric field and the variance of the electric field oscillates at the double carrier frequency (Fig. 1a). How such a non-classical electric field can affect the dynamics of photoemitted electrons was theoretically demonstrated recently [4]. Furthermore, the photon-number distribution of BSV has a very long tail in contrast to coherent light. These photon-number distributions can be imprinted onto the photon statistics of optical harmonics [3] and the statistics of electrons [5].
CRIS-Team Scopus Importer:2025-09-26

Strong-field electron emission from gold needle tips - Heimerl, Jonas; Meier, Stefan; Kirchner, Adrian; Weitz, Tobias; Hommelhoff, Peter (Journal of Vacuum Science & Technology B, Nanotechnology and Microelectronics, 2023)
We show strong-field electron energy spectra from nanometric gold needle tips triggered by femtosecond laser pulses. For this, we use two different wavelengths, 800 nm with 12 fs pulse duration and 1550 nm with 170 fs pulse duration. With an extended plateau and cutoff of rescattered electrons, the recorded electron spectra show the tell-tale features of strong-field physics. Furthermore, the spectra clearly show above-threshold photoemission peaks. Such energy spectra are an ideal tool to benchmark current theory models.
Created from Fastlane, Scopus look-up